Penerapanan Metode Beyond Centers And Circle Time (Bcct) Pada Pendidikan Anak Usia Dini (Paud) - Robecca, Julian; Sofiani, Ratna Imanira; Hasti, Novrini (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2020)
ABSTRACT The golden age for a child is the age when he is 0 to 5 years old. At this age the child's physical development and brain growth optimally. Children's brain development related to intelligence requires stimulation from the surrounding environment. If stimulation from the environment is lacking, the child's intellectual development is also not optimal. To increase stimulation from an early age many Early Childhood Education (PAUD) have emerged, which is a form of educational institution which is an artificial environment that is consciously designed and planned to develop children's intelligence potential. From 2013 data, the Directorate General of Early Childhood, Non-Formal and Informal Education (PAUDNI) Bandung has 1,323 PAUD. From all of these methods there is one concept that is the benchmark in the PAUD program, namely that education must be fun and in accordance with the child's development. The BCCT method develops from the Montessori, High Scope and Region Emilio methods. The purpose of community service activities is to create teachers who can apply BCCT learning methods to students, assist teachers in the delivery of learning materials that are appropriate to the child's development, help children in the reception and absorption of learning materials, create a pleasant atmosphere in the learning process for both partners . Key words: Early Childhood Education, Beyond Centers and Circle Time (BCCT), golden age, ABSTRAK Golden age bagi seorang anak adalah usia ketika dia berusia 0 hingga 5 tahun. Pada usia ini perkembangan fisik dan otak anak tumbuh secara optimal. Perkembangan otak anak yang berkaitan dengan kecerdasan membutuhkan stimulasi dari lingkungan sekitarnya. Jika stimulasi dari lingkungan kurang, perkembangan intelektual anak juga tidak optimal. Untuk meningkatkan stimulasi sejak usia dini banyak bermunculan Pendidikan Anak Usia Dini (PAUD), yaitu suatu bentuk lembaga pendidikan yang merupakan lingkungan buatan yang secara sadar dirancang dan direncanakan untuk mengembangkan potensi kecerdasan anak. Dari data tahun 2013, Direktorat Jenderal Pendidikan Anak Usia Dini, Nonformal dan Informal (PAUDNI) Bandung ada 1.323 PAUD. Dari semua metode ini ada satu konsep yang menjadi tolok ukur dalam program PAUD, yaitu bahwa pendidikan harus menyenangkan dan sesuai dengan perkembangan anak. Metode BCCT mengembang dari metode Montessori, High Scope dan Regio Emilio. Tujuan kegiatan pengabdian masyarakat adalah, menciptakan guru yang dapat menerapkan metode pembelajaran BCCT pada siswa, membantu guru dalam penyampaian materi pembelajaran yang sesuai dengan perkembangan anak, membantu anak-anak dalam penerimaan dan penyerapan bahan belajar, menciptakan suasana yang menyenangkan di proses pembelajaran pada kedua pasangan. Kata kunci: Beyond Center Circle Time (BCCT), golden age, Pendidikan Anak Usia Dini (PAUD),